2017
DOI: 10.12681/bgsg.11270
|View full text |Cite
|
Sign up to set email alerts
|

Active Tectonics in the Hellenic Volcanic Arc: The Kolumbo Submarine Volcanic Zone

Abstract: This paper studies the rupture system of the Anydhros

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 9 publications
0
31
0
Order By: Relevance
“…Tibaldi et al (2008) suggest that Nisyros volcanic field has developed within a major NE-trending graben with strong evidence of left-lateral strike-slip component. In accordance to that, Sakellariou et al (2010) have proposed that the Santorini-Koloumbo volcanic field has developed within and along the transtensional NE-SW trending Anydros basin and that the volcanic centers of Christiana, Kameni and Koloumbo are aligned along a major strike-slip fault-zone. Piper & Perissoratis (2003) have shown that the offshore area north and south of Milos is strongly offset by prominent N-S faults and at least one major NE-trending active fault and argue that this fault pattern is a consequence of NE-trending sinistral shear.…”
Section: South Aegean Seamentioning
confidence: 62%
See 1 more Smart Citation
“…Tibaldi et al (2008) suggest that Nisyros volcanic field has developed within a major NE-trending graben with strong evidence of left-lateral strike-slip component. In accordance to that, Sakellariou et al (2010) have proposed that the Santorini-Koloumbo volcanic field has developed within and along the transtensional NE-SW trending Anydros basin and that the volcanic centers of Christiana, Kameni and Koloumbo are aligned along a major strike-slip fault-zone. Piper & Perissoratis (2003) have shown that the offshore area north and south of Milos is strongly offset by prominent N-S faults and at least one major NE-trending active fault and argue that this fault pattern is a consequence of NE-trending sinistral shear.…”
Section: South Aegean Seamentioning
confidence: 62%
“…6. Interpretation of single channel seismic profiles obtained by HCMR during the last decades ( Figure 2) in the frame of several projects and cruises: HERMES -south and southwest Crete, KM3Net -Southwest Peloponnese, THERA -Santorini area (Sigurdsson et al, 2006;Sakellariou et al, 2010), Gulf of Corinth (Moretti et al, 2004;Lykousis et al, 2007;Sakellariou et al, 2007a), AMPHITRITE -North Evia Gulf (Sakellariou et al, 2007b), North and South Ikarian Basins (Lykousis et al, 1995) and other ( Figure 2). 7.…”
Section: Methodsmentioning
confidence: 99%
“…[] and Sakellariou et al . [] propose that the basin is bounded by two overlapping dextral strike‐slip faults, which may have controlled the spatial distribution of the volcanic centers of the Santorini volcanic field. Direct evidence of such faults (e.g., flower structures) have not, however, been observed in multichannel seismic reflection profiles [ Hübscher et al ., ].…”
Section: Geological and Geophysical Settingmentioning
confidence: 99%
“…Seismic reflection profiles indicate that the south, north, and west basins of the caldera are underlain by >200 m of stratified material which Sakellariou et al . [] have divided into six subunits. Sakellariou et al .…”
Section: Geological and Geophysical Settingmentioning
confidence: 99%
“…Piper and Perissoratis (2003) provided a synthetic map of both, new and previously known, offshore faults in the South Aegean Sea. Swath bathymetry and single channel seismic profiles have been used to map the faults in the area of Nisyros and Kos Islands (Tibaldi et al, 2008;Nomikou and Papanikolaou, 2011), around Santorini (Sakellariou et al, 2010) and in Christiana Basin, between Santorini and Milos Islands (Tsampouraki-Kraounaki et al, 2015).…”
Section: Introductionmentioning
confidence: 99%